The impact of audit fees and auditor tenure on company valuation: An analysis of large U.S. audit firms. - Santos-Jaén, José Manuel; Valls Martínez, María del Carmen; Martín de Almagro Vázquez, Gema; León-Gómez, Ana María (Elsevier, 2025)
This study aims to investigate the impact of audit fees and auditor tenure on company valuation, focusing on large U.S. audit firms. It examines how these factors influence firm value as measured by Tobin’s Q, providing insights into the broader implications of financial governance practices on investor perceptions and market dynamics. The research employs a panel data regression methodology and the generalized method of moments (GMM) to analyze data from companies included in the S&P 500 index over the period 2012 to 2021. This approach allows for robust statistical analysis and controls for potential autocorrelation and heteroscedasticity issues in the dataset. The findings indicate that auditor tenure does not have a statistically significant impact on corporate value. This suggests that the length of the audit engagement, in isolation, may not materially influence how investors perceive the reliability of financial reports. However, lower audit fees may indicate efficient cost management, which is positively perceived by the market. This study contributes to the auditing literature by providing empirical evidence on the relationship between auditor tenure, audit fees, and company valuation. It highlights the importance of implementing efficient audit fee structures to enhance firm value, offering practical implications for corporate governance and policy formulation. By demonstrating the positive impact of audit practices on firm value, this study underscores the broader social benefit of financial transparency and integrity, fostering a trustworthy investment environment and contributing to the overall health of the economy. Auditing is increasingly essential in company valuation as it underpins financial integrity and transparency, creating a trustworthy and secure environment for investors that improves the company’s value in the market.
Keywords: Econometría; Método de momentos (Estadística); Auditoría; Análisis de datos de panel; Auditor Tenure; Audit Fees; Company Value; Tobin’s Q; Panel data regression; Generalized Moment Method